Drone Larvae Homogenate (Apilarnil) as Natural Remedy: Scientific Review - Sibel Silici (Journal of Agricultural Sciences)
For centuries, honey bee products such as honey, bee pollen, royal jelly, bee bread (Perga), and bee venom have been utilized in natural medicine due to their beneficial properties. A great deal of scientific research has been dedicated to exploring their physico-chemical properties and therapeutic effects. Despite this, drone larvae have not received as much attention from the scientific community. Within a honey bee colony, drones are responsible solely for fertilizing queen bee eggs and consuming food reserves collected by worker honey bees. As a result, beekeepers commonly remove excess drone brood from the hive, which is crucial for preventing and treating varroasis. Lyophilization is the most effective method for preserving drone larvae, and the physicochemical properties of fresh and lyophilized drone larvae were compared. The therapeutic effects of drone larvae, such as androgenic, hepatoprotective, immunostimulatory, and hypolipidemic effects in humans and experimental animals, were summarized. This study aims to summarize current scientific knowledge on drone larvae (apilarnil). The author utilized well-known publication databases like SCOPUS, Google Scholar, and Pub Med to gather research on drone larvae. Furthermore, this review collected information on the chemical composition preservation and bioactive action of drone larvae. Thanks to their high levels of amino acids, fatty acids, vitamins, minerals, and hormones, drone larvae can be considered a potential potency-raising agent.